Pre-service Early Childhood Teachers' Challenges and Solutions to Planning and Implementing STEM Education-Based Activities - Ciftci, Ayse; Topcu, Mustafa Sami (SPRINGER, 2022)
This paper aims to explore the challenges that pre-service early childhood teachers (PECTs) face in the processes of planning and implementing STEM education-based activities and their solutions about these challenges. A total of 39 third-year pre-service teachers in Istanbul, Turkey, participated in the study, which lasted 14 weeks. The data were collected through an open-ended questionnaire and focus group interviews. The data were analyzed via qualitative approaches and codes and themes were determined. As a result of the analysis, five themes related to the planning of STEM education-based activities emerged: identifying the problem, group works conducted by the pre-service teachers, children's development level, material selection, and STEM integration. Regarding the challenges the PECTs faced during the implementation process of STEM education-based activities, six themes emerged: expressing the problem, group works conducted by the pre-service teachers, targeted instruction and implementations, children's development level, time management, and classroom management. The analysis revealed 8 themes regarding the pre-service teachers' solutions about successful planning and implementation of STEM education-based activities: materials to be used, group works conducted by the pre-service teachers, classroom arrangement and management, time management, appropriateness to children's level, identifying and expressing the problem, activity planning and implementation, and implementing STEM education. This study is important because it will contribute to the implementation of STEM-based activities more in early childhood classes, as it identifies the challenges faced in the process of designing and implementing STEM-based activities as well as providing suggestions for the solution of these problems.
Keywords: STEM education-based activities; Planning and implementing; Challenges and solutions; Early childhood education; Pre-service early childhood teachers; Education & Educational Research